“WANTING TO DIE” - VIALLA, Pr François (MEDECINE LEGALE DROIT MEDICAL, 2025)
In our societies, the boundaries of life, from terminus a quo to terminus ad quem, have become the preserve of medicine. By repressing death, both literally and figuratively, we have led to its hyper-medicalisation and to the hospitalisation of the end of life. Medicine is now caught in a trap. Unmindful of our contradictions, we ask it, through paradoxical demands, to postpone the end of life ever further, but also to accelerate it, or even to provoke it, when the end of life is in sight.